An Attempt to Identify the Scope and Principles of Good Governance - Szumowski, Witold (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The paper analyses ways of understanding good governance. The first part examines a number of definitions of the concept of good governance developed by multilateral organizations, national institutions and scientists. This is followed by a discussion of the criticism of good governance. The final section offersa universal definition of good governance and its constituent principles.